Informant similarities, twin studies, and the assessment of externalizing behavior: A meta-analysis. (April 2018) - Talbott, Elizabeth; Karabatsos, George; Zurheide, Jaime L.
Abstract: The purpose of this study was to examine similarity within informant ratings of the externalizing behavior of monozygotic (MZ) and dizygotic (DZ) twin pairs. To do this, we conducted a meta-analysis of correlations within ratings completed by mothers, fathers, teachers, and youth. We retrieved n = 204 correlations for MZ twins and n = 267 correlations for DZ twins from n = 54 studies containing n = 55 samples. Results indicated that all four informants were significant negative predictors of within-informant correlations in their ratings of MZ, but not DZ twins. In the case of longitudinal studies and as the age of MZ twins increased, similarity within ratings by mothers was significantly greater than similarity within ratings by fathers. Among participant characteristics, we found that (a) age was a significant negative predictor of similarity within ratings for MZ twins; (b) race was a significant predictor of similarity within ratings for both MZ and DZ twins, but in the opposite direction; and (c) DZ opposite sex twins were a significant negative predictor of within-rating similarity. Among study characteristics for MZ twins, participant group and longitudinal study were significant negative predictors of within-rating similarity, and for both MZ and DZ twin pairs, non-independence in the data was a significant negative predictor of within-rating similarity. For DZ twins, multiple informants were significant positive predictors of within-rating similarity, and in longitudinal studies with DZ twins, similarity within ratings by mothers was significantly greater than similarity within ratings by fathers, and similarity within ratings by fathers was significantly less than similarity within ratings by teachers and youth. For both MZ and DZ twins, the following study characteristics were significant positive predictors of similarity within ratings: study group, number of time points, and multiple constructs. All four informants appeared equally skilled at predicting within-informant correlations for MZ (but not DZ) twins, with participant characteristics having different predictive effects for MZ compared to DZ twins, and study characteristics having comparable predictive effects for both twin types. Overall, these findings suggest effective discrimination on the part of four informants who rated the externalizing behavior of MZ and DZ twins.